Business Plan of Laveena (Journal of Business and Management, 2022)
Clothing has become a basic human need. As a country with a majority Muslim population, Muslim fashion in Indonesia is growing rapidly. Muslim fashion products are in great demand by the Indonesian population.Laveena as a clothing fashion brand in Indonesia that focused on Muslim markets certainly has a great opportunity. During its business journey since 2021, Laveena has managed to sell hundreds of products and ship to more than 500 customers to more than 20 province all over Indonesia. There are obstacles appear and lead to an impact on sales performance. To maintain business and increase sales, Laveena must develop a business strategy. On the marketing aspect, a new strategy is made based on the results of marketing research. Laveena will focus on social media marketing activities maximizing Instagram @laveena.co which has chosen more than 16K followers to influence customer purchase intentions for Laveena products. Laveena also made changes to the production plan, switching from working with a third party as a production vendor to becoming an own production system. Laveena will recruit employees to be able to carry out all business activities professionally.The business plan will use Rp52.800.000 as the initial capital, this fund is coming from Laveena investment and business activities profit in 2021. By implementing this business strategy Laveena is expected to earn Rp52.000.000/month as gross profit and Rp42.000.000/month as net profit at the end of 2022.Keywords: Laveena; Business Plan; Social Media Marketing Activities